Representasi Sabda Pandhita Ratu Raja Jawa dalam Wayang Purwa Lakon Kresna Duta - Rio Candra; Sucipto Hadi Purnomo (Universitas Syiah Kuala, 2025)
Sabda pandhita ratu (the decree of a sage-king) is a principle upheld by a king. However, in wayang kings are often depicted as violating this principle. This study aims to reveal the representation of the sabda pandhita ratu concept in Javanese kings within the wayang purwa stories. The research employs a qualitative approach with a semiotic method. The data consist of signs and symbols found in wayang purwa performances. The primary data source is a wayang purwa performance featuring the Kresna Duta play by Ki Anom Suroto. Data collection was conducted using the observation and note-taking technique and analyzed through Charles Sanders Peirce's semiotic model, which includes the representamen, object, and interpretant. The findings indicate that in the Kresna Duta play, the sabda pandhita ratu in Javanese kingship is upheld by Kresna and Karna, then rejected by Duryudana. Duryudana's denial of the sabda pandhita ratu is driven by greed, pressure, and political interests. This rejection leads to negative political consequences and tarnishes a leaders integrity.